Optoplasmonic networks with morphology-dependent near- and far-field responses. (21st December 2015) - Ahn, Wonmi; Zhao, Xin; Hong, Yan; Reinhard, Björn M.
Abstract: Abstract : Optoplasmonic networks consisting of dielectric microsphere resonators and plasmonic nanoantennas in a morphologically well-defined on-chip platform support unique electromagnetic signatures that are hybrids of photonic whispering gallery modes and localized surface plasmon resonances. Here we explore the dependence of their near- and far-field responses on the key structural parameters, including the size of the gold nanoparticles forming the plasmonic elements, the separation between the microspheres, and the geometry of the chain. The high degree of structural flexibility, which is experimentally accessible through template guided self-assembly approaches, makes these optoplasmonic structures a unique electromagnetic material for tuning spectral shapes and intensities.